Assessment of consequences of impact of emergency explosion of fuel-air mixture on a person - Ivanitskiy, Александр; Petriko, Елена (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2014)
The comparative analysis of existing dependences is provided according to impact of explosion overpressure on a person therefore it is established that the values of probabilities received at calculation have considerable distinctions. The review of experimental research is presented in range of definition of impact of explosion overpressure on a person. The method of carrying out of experimental research for definition of impact of explosion overpressure on a person is presented.